1 | initial version |

The author of this question intends for you to plug 5 in for x and k in for y. If you do this, you will obtain

2(5) + k - 7 = 0 10 + k - 7 = 0 3 + k = 0 k = -3

We can check our work by confirming that (5, -3) is a solution to 2x + y - 7 = 0. 2(5) + (-3) - 7 = 10 - 3 - 7 = 7 - 7 = 0.

2 | No.2 Revision |

The author of this question intends for you to plug 5 in for x and k in for y. If you do this, you will obtain

2(5) + k - 7 = ~~0
~~0

10 + k - 7 = ~~0
~~0

3 + k = ~~0
~~0

k = -3

We can check our work by confirming that (5, -3) is a solution to 2x + y - 7 = 0.

2(5) + (-3) - 7 = 10 - 3 - 7 = 7 - 7 = 0.

Copyright Sage, 2010. Some rights reserved under creative commons license. Content on this site is licensed under a Creative Commons Attribution Share Alike 3.0 license.